PSYCOPATHIC DISORDER IN DAVID BALDACCI ‘S THE WINNER - Septiana, Tiyas Widya (LANTERN (Journal on English Language, Culture and Literature), 2016)
This thesis analyzes David Baldacci’s novel entitled The Winner. The purposes of this thesis are to explain about the cause of psychopathic disorder, the characteristics of a psychopath, and the effect of psychopathic disorder. The methods that are used in this thesis are library research and psychological approach. This analysis shows the cause of psychopathic disorder of the antagonist, those are childhood harassment and bullying. He has the characteristics of a psychopath: glibness/superficial charm, grandiose sense of self-worth, need for stimulation/proneness to boredom, pathological lying, conning/manipulative, lack of remorse or guilt, lack of empathy, and early behavioral problems. Then, the effect of his psychopathic disorder is not only for himself but also his surroundings. In summary, this thesis shows that psychopathic disorder brings bad impact not only for the sufferer, but also his surroundings. It is shown from how the psychopathic disorder ruins the sufferer’s personality and gives impacts on how he acts towards his surroundings.